Tradisi Besentulak di Lombok: Kajian Living Qur’an - Firda, Firda Hutami Putri (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This article discusses the Besentulak (Tolak Bala) tradition in Lombok, particularly in Batu Kuta Village, through the perspective of the Living Qur’an approach. The study aims to explore how the values of Qur’anic teachings especially the command to recite shalawat upon the Prophet Muhammad SAW are manifested in the socio-cultural practices of the local community. This research employs a qualitative method with an ethnographic approach. Data were collected through in-depth interviews and documentation to capture the lived religious experiences of the community. The findings reveal that the recitation of shalawat in the Besentulak tradition represents an actualization of Qur’anic values embedded in everyday life. This practice functions not only as a spiritual means of seeking protection, safety, and well-being, but also as a medium for strengthening social cohesion, preserving inherited religious traditions, and contextualizing Islamic teachings within local cultural expressions. The study demonstrates that the practice of the Living Qur’an in Batu Kuta Village is reflected in the continuity of religious traditions rooted in the Qur’an while remaining harmoniously integrated with local customs and communal identity.